Hydroclimate Variability Influenced Social Interaction in the Prehistoric American Southwest - Gauthier, Nicolas (Frontiers in Earth Science, 2021)
When droughts and floods struck ancient agrarian societies, complex networks of exchange and interaction channeled resources into affected settlements and migrant flows away from them. Did these networks evolve in part to connect populations living in differing climate regimes? Here, I examine this relationship with a long-term archaeological case study in the pre-Hispanic North American Southwest, analyzing 7.5 million artifacts from a 250-year period at nearly 500 archaeological sites. I use these artifacts to estimate how the flow of social information changed over time, and to measure how the intensity of social interaction between sites varied as a function of distance and several regional drought patterns. Social interaction decayed with distance, but ties between sites in differing oceanic and continental climate regimes were often stronger than expected by distance alone. Accounting for these different regional drivers of local climate variability will be crucial for understanding the social impacts of droughts and floods in the past and present.